A new species of Laurenceomyia Wagner & Stuckenberg, with a key to species and new records for Psychodidae (Diptera) from Uruguay - Canneva, Bruno (Zootaxa, 2019)
A species list and a key to species of Psychodidae (Diptera, Nematocera) from Uruguay is presented, with the description of Laurenceomyia martinezae sp. nov., and first records of Brumptomyia guimaraesi (Coutinho & Barreto), Nyssomyia neivai (Pinto), Paramormia furcata (Kincaid), Psychoda savaiiensis Edwards, Psychoda zetoscota Quate, and Trichomyia Haliday in Curtis. Discussion on the medically important species is provided.